The blood count as a compass to navigate in the ever-changing landscape of the carrier state of hemoglobinopathies: a single-center Italian experience - Marchesani, Silvio; Di Mauro, Margherita; Ceglie, Giulia; Grassia, Ginevra; Carletti, Michaela; Cristofaro, Rosa Carmela; Cossutta, Matilde; Curcio, Cristina; Palumbo, Giuseppe (Frontiers in Pediatrics, 2023)
Introduction Approximately 7% of the worldwide population exhibits variations in the globin genes. The recent migration of populations from countries where hemoglobin disorders are endemic has resulted in important epidemiological changes with the diffusion of newly discovered or poorly characterized genetic variants and new combinations and very heterogeneous clinical phenotypes. The aim of our study is to assess the parameters that are more significant in predicting a positive genetic testing outcome for hemoglobinopathies in a pediatric population of patients presenting with anemia or microcythemia, without a definite diagnosis. Methods and materials This study included patients evaluated in our hematological outpatient clinic for anemia and/or microcythemia despite normal ferritin levels. A screening of pathological hemoglobins using high-performance liquid chromatography (HPLC) was performed for the entire population of the study. Subsequently, patients with hemoglobin (Hb) S trait and patients with an HPLC profile compatible with beta thalassemia trait were excluded from the study. Genetic screening tests for hemoglobinopathies were performed on the remaining patients, which involved measuring the red blood cell (RBC) counts, red blood cells distribution width (RDW), reticulocyte count, and mean corpuscular volume of reticulocytes (MCVr). Results This study evaluated a total of 65 patients, consisting of nine patients with negative genetic analysis results and 56 patients with positive genetic analysis results. The Hb and RDW values in these two groups did not demonstrate statistical significance. On the other hand, there were statistically significant differences observed in the mean corpuscular volume (MCV), RBC count, reticulocyte count, and MCVr between the two groups. Furthermore, in the group of patients with positive genetic test results, specific genetic findings associated with different HPLC results were observed. In particular, 13 patients with positive genetic test results had normal HPLC findings. Discussion This study has demonstrated that HPLC, while serving as a valuable first-level test, has some limitations. Specifically, it has been observed that some patients may exhibit a negative HPLC result despite a positive genetic analysis. In addition to the presence of low levels of Hb and HPLC alterations, other parameters could potentially indicate the underlying mutations in the globin genes. Therefore, we propose that the complete blood cell count be utilized as a widely available parameter for conducting targeted genetic analyses to avoid the risk of overlooking rare hemoglobinopathies.